How placental growth factor detection might improve diagnosis and management of pre-eclampsia. (May 2014) - Duhig, Kate E; Chappell, Lucy C; Shennan, Andrew H
<x xml:space="preserve">Abstract</x> Pre-eclampsia complicates around 5% of pregnancies and hypertensive disorders of pregnancy are responsible for over 60, 000 maternal deaths worldwide annually. Identifying women with pre-eclampsia is a major goal of antenatal care in order to target increased surveillance, allow stabilizing therapies to be implemented and to enable timely delivery. Current risk assessment is based on clinical history, imperfect assessment of clinical signs (e.g., hypertension and proteinuria) and nonspecific biochemical markers, all of which are subject to considerable error. This is further confounded by underlying maternal disease such as chronic hypertension or renal pathology. Angiogenic factors reflect the underlying pathophysiology of pre-eclampsia and there is emerging evidence that they can now be used for more accurate risk assessment. The most promising of these factors include placental growth factor and soluble fms-like tyrosine kinase-1. Used at point of care, these can accurately discriminate true disease in suspected cases and subsequent need for delivery.